2018
DOI: 10.1159/000492532
|View full text |Cite
|
Sign up to set email alerts
|

Omalizumab in Chronic Urticaria: An Italian Survey

Abstract: Omalizumab is approved for use in chronic spontaneous urticaria (CSU); however, it is not approved for chronic inducible urticaria (CIndU). The aim of the present study was to assess the effectiveness of omalizumab in treating CSU and CIndU in Italy. This is a multicentre prospective observational real-life study involving patients with severe urticaria capable of undergoing omalizumab therapy. We enrolled 127 patients (59.1% females), ranging in age from 15 to 83 years, 69.3% had CSU alone, 26.8% had CSU and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 13 publications
1
13
1
2
Order By: Relevance
“…In our study, in line with the literature (Damiani et al, ; Mandel et al, ; Nettis, ), clinical responses to the first, second, and third courses of omalizumab were similar. This characteristic is important because some patients are subject to relapses of moderate‐to‐severe degree after a course of treatment (mean disease‐free interval is about 2.5 months) and need periodic retreatment.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, in line with the literature (Damiani et al, ; Mandel et al, ; Nettis, ), clinical responses to the first, second, and third courses of omalizumab were similar. This characteristic is important because some patients are subject to relapses of moderate‐to‐severe degree after a course of treatment (mean disease‐free interval is about 2.5 months) and need periodic retreatment.…”
Section: Discussionsupporting
confidence: 92%
“…To the best of our knowledge, the time limit of 6 months for continuous treatment with omalizumab is defined only in Italian regulations. Thus, our data can be compared with those of studies performed by Italian authors (Bongiorno et al, ; Damiani et al, ; Mandel et al, ; Nettis, ; Romano et al, ). Romano et al reported a higher rate of complete resolution than in our study, but in a smaller population (6/9 patients, 67%), while Bongiorno et al reported, in a group of 18 patients, a 35.7% rate of complete resolution, followed by relapse within 1–4 months in all cases.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…so-called chronic inducible urticaria, CindU), it is named chronic spontaneous urticaria (CSU), which may include auto-immune pathogenesis. 1 First line treatment is based on second-generation antihistamines (H 1 ), which can be increased up twofold to fourfold the standard dosage to reach clinical remission (ie, second line of treatment). 2 However, in some individuals, standard therapy with antihistamines is inadequate; therefore, these patients require alternative therapeutic approaches.…”
mentioning
confidence: 99%
“…Следует заметить, что отдельного исследования по использованию омализумаба при ХСК у детей до 18 лет в мире не проводилось. Однако, есть данные реальной клинической практики, где подростки вместе со взрослыми пациентами с ХСК получали данную терапию [25]. В одном из последних метаанализов оценки эффективности и безопасности омализумаба при ХСК, в который были включены и исследования с подростками, показано, что эффек-тивность омализумаба была выше, чем в проведенных ранее плацебоконтролируемых рандомизированных исследованиях, и достигала 72% [26].…”
Section: динамикаunclassified